Strategic environmental urban planning - A contextual approach for defining performance goals and informing decision-making. (15th January 2020) - Nault, Emilie; Jusselme, Thomas; Aguacil, Sergi; Andersen, Marilyne
Abstract: Environmental performance objectives in terms of energy consumption and carbon emission targets can be found in various building norms and certifications schemes. These targets are often dependent upon the building program (e.g. office), but independent from its context; the same value is imposed for two buildings of the same program regardless of other possibly influential characteristics (e.g. solar exposure). Such targets serve as references against which a project's performance is measured following its description and assessment using an evaluation tool. In this paper, we question the suitability of this procedure within the context of urban planning by asking: should a district-level performance objective be allocated in a 'uniform' manner or through a 'contextual' approach, capable of capturing specificities throughout the site and allowing compensation between areas? To address this question, a novel method is proposed to distribute a site-level target differently between lots presenting distinct conditions over the site, through a combined top-down and bottom-up approach. The method relies on the exploration of databases of lot-specific scenarios, generated by varying design parameters that have not yet been fixed at the planning stage, such as building shape and construction materials. Applied on a case-study district in Switzerland, the contextual method results in differentiated lot-specific targets that are up to 11% away from the uniform targets. Although apparently small, these shifts can increase the feasibility of reaching the site-level target by up to 30%. Such information can guide the design team towards defining a coherent environmental strategy and making informed decisions. Highlights: A method for defining contextual environmental targets is proposed. The method relies on a workflow generating databases of context-specific scenarios. It is illustrated through application on a case-study district. Implications of applying uniform vs context-specific targets are investigated. Feasibility of reaching the site-level goal is higher for the contextual approach.